The Effect of Benson Relaxation and Peppermint Aromatherapy on Emotional Mental Disorders in Hypertension Patients - Wahyudi Qorahman MM; Zuliya Indah Fatmawati; Robby Steven (Indonesian Journal of Global Health Research, 2024)
Emotional mental disorders in individuals with hypertension can worsen their physical condition and reduce the success of their treatment. Effective interventions are needed to address emotional mental disorders in hypertension patients. One non-pharmacological method that has been studied is the combination of Benson relaxation techniques and peppermint aromatherapy. Objective: This study aims to evaluate the effects of Benson relaxation and peppermint aromatherapy on emotional and mental disorders in hypertension patients. Method: This research used a quasi-experimental design with a pre-test and post-test control group. A total of 30 hypertension patients with emotional mental disorders were selected through random sampling and divided into intervention and control groups. The intervention consisted of Benson relaxation techniques and peppermint aromatherapy. Measurements were conducted using the SRQ-20 questionnaire to evaluate emotional mental disorders before and after the intervention. Data analysis included paired-sample T-tests to compare pre-test and post-test results, as well as Mann-Whitney tests for comparisons between the intervention and control groups. Results: The study results showed that Benson relaxation and peppermint aromatherapy were significantly effective in reducing emotional mental disorders in hypertension patients, with a P value = 0.001 (P ≤ 0.05). There was a significant difference between the intervention and control groups, with the intervention group demonstrating better results in reducing emotional mental disorders. Conclusions: This study concludes that Benson relaxation and peppermint aromatherapy are significantly effective in reducing emotional mental disorders in hypertension patients. This intervention can serve as a potential non-pharmacological approach and complement conventional medical treatments, offering holistic benefits in hypertension management.